Personu nereabilitējošo apstākļu kriminālprocesuālais institūts - Dzelme, Māris (Latvijas Universitāte, 2018)
Atslēgas vārdi: personu nereabilitējošie apstākļi, nereabilitēšana; nereabilitēšanas nosacījumi; nereabilitēšanas tiesiskās sekas; vaina, vainas pierādīšana/konstatēšana, vainas atzīšana, sods, sodāmība, tiesību ierobežošana, kriminālprocesa izbeigšana/pabeigšana.

The Master’s thesis “The institution of criminal proceedings of circumstances that do not exonerate a person” focuses on the regulation of the circumstances that do not exonerate the person in the Criminal Procedure Law of the Republic of Latvia, the theoretical aspects of the circumstances that do not exonerate the person, the institution of circumstances that do not exonerate the person, as well as the legal consequences of the circumstances that do not exonerate the person in the narrowest and broadest sense. The research seeks the answers to the following research questions: a) What the circumstances that do not exonerate the person mean; b) What legal effects are caused by the circumstances that do not exonerate the person; c) Whether the circumstances that do not exonerate the person end; d) Should the circumstances that do not exonerate the person end. During the process of the development of the Master's thesis, the author of the thesis concludes, firstly, that the person's non-exoneration is based on his recognition as being found guilty of committing a criminal offense, secondly, in the criminal proceedings the main substantive condition of the person’s non-exoneration is finding a person guilty of committing a criminal offense but the procedural condition – finding of guilt, thirdly, the circumstances that do not exonerate the person cause criminal and non-criminal consequences, fourthly, the status of the person not exonerated is without the period of limitation or the person will be considered guilty of committing a criminal offense, as long as he is not exonerated. In the Master's thesis and in its summary, the author points to some issues of applying some legal provisions, discontinuing the criminal proceedings on the basis of not being exonerated. Key words: circumstances that do not exonerate a person, non-exoneration; conditions of non-exoneration, legal consequences of non-exoneration, guilt, proof/finding of guilt, admission of guilt, penalty, criminal conviction, disqualification, termination/completion of the criminal proceedings.
The institution of criminal proceedings of circumstances that do not exonerate a person
Keywords: Juridiskā zinātne; personu nereabilitējošie apstākļi; nereabilitēšana; nereabilitēšanas tiesiskās sekas; vaina; vainas pierādīšana/konstatēšana